Vestibular Stimulation Causes Contraction of Subjective Time - Utegaliyev, Nariman; von Castell, Christoph; Hecht, Heiko (Frontiers in Integrative Neuroscience, 2022)
As the cerebellum is involved in vestibular and time-keeping processes, we asked if the latter are related. We conducted three experiments to investigate the effects of vestibular stimulation on temporal processing of supra-second durations. In Experiment 1, subjects had to perform temporal productions of 10- and 15-s intervals either standing on both feet or while being engaged in the difficult balancing task of standing on one foot with their eyes closed (or open for control purposes). In Experiment 2, participants were required to produce intervals of 5, 10, 15, and 20 s while standing on both feet with their eyes open or closed, which constituted an easier balancing task. In Experiment 3, we removed the active balancing; temporal productions of the same four durations had to be performed with the eyes open or closed during the passive vestibular stimulation induced by the oscillatory movements of a swing. Participants produced longer intervals when their eyes were closed, but active balancing was not the culprit. On the contrary, temporal over-production was particularly pronounced during the passive vestibular stimulation brought about by the swing movements. Taken together, the experiments demonstrate that the contraction of the subjective time during balancing tasks with closed eyes is most likely of vestibular origin.